2007
DOI: 10.1002/ajim.20523
|View full text |Cite
|
Sign up to set email alerts
|

Pesticide use and chronic bronchitis among farmers in the agricultural health study

Abstract: Background-Farmers have increased risk for chronic bronchitis. Few investigators have considered pesticides.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
71
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(77 citation statements)
references
References 43 publications
3
71
0
3
Order By: Relevance
“…The AHS cohort has given rise to a series of studies on exposure to specific pesticides and showed that numerous pesticides were significantly associated with allergic asthma [52], wheeze [49,51] and chronic bronchitis [58]. It was also shown that accidental exposure or pesticide poisoning were associated with an increased risk of allergic and nonallergic asthma [59].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The AHS cohort has given rise to a series of studies on exposure to specific pesticides and showed that numerous pesticides were significantly associated with allergic asthma [52], wheeze [49,51] and chronic bronchitis [58]. It was also shown that accidental exposure or pesticide poisoning were associated with an increased risk of allergic and nonallergic asthma [59].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, assessment of exposure is also generally based on self-reports. However, some studies [37,38,44,46,47,58] assessed cumulative lifetime exposure to pesticides, while others asked about specific pesticides used [32,37,64,65] or specific crops [34,56], allowing a more precise definition of exposure. Finally, even for asthma, it is difficult to establish a causal relationship with exposure to pesticides.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although agricultural workers show no symptoms of cholinergic toxicity, they are clearly absorbing OPs, as their blood AChE and butyrylcholinesterase activity were diminished (10,11). In these workers, OP exposure correlated with an increase in cough (11), wheeze (11,12), and bronchitis (13), and a decrease in lung function (10,11).…”
Section: Clinical Relevancementioning
confidence: 99%
“…These include organic dusts and other respiratory hazards that include inorganic dusts, pesticides and agrochemicals [9]. Farmers and individuals involved in agricultural work have potential exposure to a very wide range of agents-inorganic dusts from soil, organic dusts from microorganisms, mycotoxins, allergens, pesticides, etc.…”
Section: Introductionmentioning
confidence: 99%